Las manualidades con materiales reciclables para el desarrollo de la creatividad de los niños de tercer grado de educación general básica en el área de ciencias naturales de la Unidad Educativa Ángel Polibio Chaves, provincia Bolívar, cantón Guaranda, periodo académico 2022-2023. - Collay Yanchaliquin, Nelly Yolanda (2023)
This research report was carried out based on the theme: Crafts with recyclable material for the development of creativity of children in the third year of basic general education in the area of natural sciences of the Angel Polibio Chaves Unit, Bolívar Province, Canton Guaranda, academic period 2022-2023, within the general objective was raised, to determine that crafts with recyclable materials contribute to the development of creativity of children in third grade of basic general education in the area of natural sciences. Crafts with recyclable material help children develop their creativity, putting their autonomy into practice and having a great capacity to function in the environment that surrounds them, applying their previous knowledge with the knowledge they acquire in the classroom. The methods used for the development of the research were: quantitative, deductive because they allowed us to obtain the necessary information to make the corresponding conclusions and the proposal. On the other hand, the instruments used were the survey that was applied to 39 children with closed questions, and the interview with a six-question questionnaire addressed to the teacher to obtain more information that is presented in the aforementioned unit or on the variables of study, focusing on our research. Through crafts we can develop the capacity for abstraction, critical thinking, putting into practice their skills, knowledge since children from their first years of life tend to be curious and develop unique abilities, therefore, the teacher plays a fundamental role in the process. of teaching leaving them to carry out recreational activities freely.